The catch - Harris, Lisa, 1969- (Harris, Lisa, 1969- US Marshals, 2022)
"An Amber Alert meant to rescue a child puts two lives in danger, forcing Madison and Jonas into a race to find a woman who wants to stay hidden, a baby who needs to be found, and a murderer they've been tracking for years"--